No Influence of Dopamine System Gene Variations on Acute Effects of MDMA - Vizeli, Patrick; Liechti, Matthias E. (Frontiers in Psychiatry, 2019)
3,4-Methylenedioxymethamphetamine (MDMA, ecstasy) is a recreational substance also investigated as medication for post-traumatic stress disorder. Dopamine (DA) system stimulation likely contributes to the acute mood effects of amphetamines including MDMA. Genetic variants such as single-nucleotide polymorphisms (SNPs) and polymorphic regions of the DA system genes may in part explain interindividual differences in the acute responses to MDMA in humans. We characterized the effects of common genetic variants within genes coding for key players in the DA system including the dopamine D2 receptor (DRD2/ANKK1 rs1800497, DRD2 rs6277, and rs107959), the dopamine transporter (DAT1 rs28363170, rs3836790, rs6347, rs11133767, rs11564774, rs460000, and rs463379), and dopamine D4 receptor(DRD4, variable-number tandem repeat [VNTR]) on the subjective and autonomic response to MDMA (125 mg) in pooled data from randomized placebo-controlled cross-over studies in a total of 149 healthy subjects. Plasma concentrations of MDMA were used as covariate in the analysis to control for individual pharmacokinetic (metabolic and weight) differences. None of the tested genetic polymorphisms within the DA system altered effects of MDMA when adjusting for multiple comparisons. Genetic variations in genes coding for players of the DA system are unlikely to explain inter-individual variations in the acute effects of MDMA in humans.